Disasters, hazards and law - Deflem, Mathieu (Sociology of crime, law, and deviance ;, 2012)
This volume deals with important social-science issues of law and legal control pertaining to disasters and hazards in a variety of contexts. The orientation of this volume is driven by relevant recent occurrences, such as hurricanes Katrina and Irene in the United States; the 2010 BP oil spill, and the 2011 Japanese earthquake and tsunami. Thematically diverse within the province of the social and behavioral sciences related to law and law-related problems, the chapters in this volume are not restricted in terms of theoretical approach and methodological orientation. Topics addressed include: legal controls pertaining to disaster prevention, response, and mitigation; regulations and policies concerning hazardous conditions; and crime and the control thereof in post-disaster situations.